Meeting the Challenge of Ecoregional Research. An International Workshop on Organizing and Managing Ecoregional Programs, Wageningen, The Netherlands 26-28 March 2001 - International Service for National Agricultural Research (International Service for National Agricultural Research, 2001)
Ecoregional Programs (ERP) were initiated by the Consultative Group on International Agricultural Research (CGIAR) in the early 1990s to improve the management of natural resources in collaboration with national and regional partners. The programs focus on specific ecological and geopolitical regions and seek a balanced emphasis on production, natural resource management and social equity. Three studies and a workshop were organized to advance thinking and practice in the organization and management of ERPs and to make suggestions for future action. An analytical description of 7 ERPs was prepared. Conclusions were drawn from an analysis of previous reviews and evaluation of ERPs. Managers of ERPs in the CGIAR and national R&D organizations were surveyed to obtain their views on organizational and management issues. During the workshop, this information was discussed, strengths and weaknesses in the organization and management of ecoregional programs were identified and, and lessons were drawn for improving of future ecoregional programs. These studies were published, along with a general report and a communiqué that summarize the overall study's results and present recommendations to strengthen the management of the ERPs.